Bored Pile Foundation Analysis Using the Meyerhof Method - Lonan, Pendekar Trio; Pinasang, Denny; Kabo, Don; Maluw, Fandel; Mantiri, Nixon; Tombokan, Franky; Mentang, Sudenroy (Jurnal Multidisiplin Madani, 2024)
The building structure can be said to be safe if supported by a strong foundation, so it is necessary to calculate the bearing capacity of the foundation using bored piles based on sondir data, calculate the load received by the pile cap, and calculate the amount of pile cap reinforcement. The method used is analytical and descriptive, while for the calculation of the foundation using the Meyerhoff method. The foundation analyzed is a bored pile foundation with a diameter of 0.4 m and a depth of 7 m. The results of the study, the type of native soil from Tomohon, North Sulawesi according to the USCS classification is soft clay with a bored pile bearing capacity of Qg = 177.45 tons. For the maximum axial force on the pile of 421.02 kN with a shear strength of 447.214 kN. The pile cap reinforcement obtained is reinforcement with a diameter of 19 mm with a distance between reinforcement of 200 mm and a used reinforcement area of ​​1134.11 mm2. The shrinkage reinforcement used is Ø12 with a distance between reinforcement of 160 mm. The substructure of a building should begin with a soil and location investigation to determine the characteristics of the soil on which a building will be built